Pengaruh Profitabilitas, Leverage, Likuiditas, Collateralizable Assets, Dan Pertumbuhan Aset Terhadap Kebijakan Dividen - Novita Rahmawati Putri; Ai Hendrani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Investors are interested in investing in a company because of its dividend policy, which affects the company's operations. A good dividend policy can provide benefits for investors in the form of dividend income. This study aims to further analyze the influence of profitability, leverage, liquidity, collateralizable assets, and asset growth on dividend policy in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022. The research method uses multiple linear regression analysis conducted using SPSS software. The purposive sampling technique was used to obtain a sample, resulting in 18 companies that met the criteria, so that the total research sample was 72 data. The results of the study showed that liquidity had no effect on dividend policy. On the other hand, profitability, leverage, collateralizable assets, and asset growth had a negative and significant effect on dividend policy. Keywords: Profitability, Leverage, Liquidity, Collateralizable Assets and Asset Growth, Dividend Policy